Organizaciones violentas - Tilly, Charles (Sociedad y Economía, 2004)
This is an exploratory study on the emergence and expansion of non governmentviolent organizations. Its aim is to account for one of the strongest trends in the currentpractice of collective violence: the substitution of the state by other forces. The authorsuggests two basic mechanisms to explain the mentioned trend: exploitation and treasuring.The first one involves the extraction of value by violent networks; the latter implies full control over property, exploitation and allocation of resources. In both cases violence causes inequality and the  conditions for its reproduction and expansion. Violent organizations do what national states have done along history; the single difference is that they are not states.